2019
DOI: 10.3390/antibiotics8020036
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Methicillin-Resistant Staphylococcus sp. (MRS) in Different Companion Animals and Determination of Risk Factors for Colonization with MRS

Abstract: The aim of this study was to detect the prevalence of methicillin-resistant Staphylococcus sp. (MRS) in populations of companion animals that either have previously been exposed or have not been exposed to antibiotic therapy or veterinary facilities, and if owners’ healthcare profession had an influence on colonization with MRS. In addition, the antimicrobial resistance pheno- and genotype were investigated and risks for colonization with MRS were assessed. During this study, 347 nasal swabs (dogs n = 152; cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 40 publications
4
20
1
Order By: Relevance
“…In this study, S. aureus was the most frequently identified Staphylococcus spp. in both healthy and diseased cats, followed by S. felis ; this is in disagreement with previously published studies [ 26 , 31 , 32 ], which reported CoNS as the most frequently occurring species in healthy and diseased cats. S. aureus is part of the normal bacterial flora in cats, especially those who are kept in close contact with their owners, which may explain the high occurrence of S. aureus in this study [ 33 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, S. aureus was the most frequently identified Staphylococcus spp. in both healthy and diseased cats, followed by S. felis ; this is in disagreement with previously published studies [ 26 , 31 , 32 ], which reported CoNS as the most frequently occurring species in healthy and diseased cats. S. aureus is part of the normal bacterial flora in cats, especially those who are kept in close contact with their owners, which may explain the high occurrence of S. aureus in this study [ 33 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies suggested that S. cohnii is largely uninvolved in severe infections such as mastitis in dairy cows 2,4 . However, NAS may harbor a wide range of AMR genes and serve as a resistance gene reservoir for pathogenic species 9,10 . The phylogenetic analysis revealed a clear genomic distinction from other NAS species.…”
Section: Discussionmentioning
confidence: 99%
“…cohnii as well as S . urealyticus isolates of animal origin were shown to carry multiple antimicrobial resistance (AMR) genes and express phenotypic resistance to various classes of antimicrobials 9 11 . Even resistance to last resort antibiotics such as linezolid was demonstrated 12 .…”
Section: Introductionmentioning
confidence: 99%
“…There is, in general, very limited knowledge about S. cohnii . S. cohnii has been isolated from different animal species without pathology (as dogs, cattle, pet animals), from environmental samples and on rare occasions, S. cohnii has been isolated from infections in humans, indicating that some strains may have some pathogenic potential [ 19 , 20 , 21 , 22 ]. It has been shown before that this species can be intrinsically resistant to penicillins and negative for all known β-lactam resistance genes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%